PENGARUH PENYEDIAAN AIR YANG BERBEDA TERHADAP DAYA ALELOPATI TEKI (Cyperus rotundus L.) PADA PERKECAMBAHAN BIJI CABAI (Capsicum annuum L.) DAN BIJI TOMAT (Lycopersicon esculentum Mill.) - , YULIANA FARKHAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Purple nutsedge (Cyperus rotundus L.) is a weed which competes with crops for light, water, and nutrients. Purple nutsedge produce allelochemicals which inhibit seeds germination and reduces crop production. The objectives of this study were to investigate the effects of water supply on the allelopathical potency of purple nutsedge and concentrations of purple nutsedge tubers extract on chili and tomato seeds germination. Two treatments were done in this work. First was planting of nutsedge in four watering intervals, i.e. everday, every two days, every four days, to field capacity. Six replicates were made for each treatment. The plants were harvested at day 45. Measured parameter were fresh leaves weight, fresh tubers weight, and fresh roots weight. The difference among treatments were analyzed using LSD (Least Significant Difference Test) 0,05. The extract was prepared by 100 g of fresh tubers purple nutsedge milled and added 100 ml aquadest to obtain 100% extracts. Purple nutsedge tubers extract was used for seed germination test. Extracts concentration used were : 100%, 50%, 25%, and control (0%) respectively. Parameters measured germination period and germination percentage. The germination test were presented in graph. The results show that water supply affects plant growth. Potency of allelopathy also affecting water supply. The higher water supply rate, the higher potency of allelopathy. Concentration tuber extract of purple nutsedge 100% was inhibiting chili and concentration tuber extract of purple nutsedge 25%, 50%, and 100% was inhibiting tomato seeds germination.